On a variational inequality problem for a finite family of nonexpansive mappings in Hilbert spaces - Mukhamedov, Farrukh; Saburov, Mansoor (Pushpa Publishing House, Allahabad, Uttar Pradesh, India, 2010)
In this paper, we prove the strong convergence of the explicit iterative process to a common fixed point of the finite family of nonexpansive mappings defined on Hilbert space, which solves the variational inequality on the fixed points set.